MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA TUNARUNGU DENGAN MENGGUNAKAN TEKNIK SKIMMING - Putri Amna, Yosfan Azwandi, Markis Yunus (Jurnal Penelitian Pendidikan Khusus, 2013)
Read on the fact that a process of physical and psychological. Deaf child is a person who has lost the ability to hear either partially or thoroughly so that he could not use it in everyday life. This research aims to demonstrate techniques of Skimming can improve reading comprehension for children Deaf in SMK N 4 field. baseline conditions 15% to 20%. The intervention of 25% to 100%